Predictors Involved in Improving Motor Function in Patients with Putamen Bleeding with Severe Lower Limb Paralysis - SAWAJIMA, Yuki; ADACHI, Hirotaka; YABE, Hiroki; TANAKA, Yoshihiro (Physical Therapy Japan, 2022)
Objective: The purpose of this study is to clarify the predictors involved in improving motor function in patients with putamen bleeding who have severe lower limb movement disorder.Method: The participants were 42 patients with putamen bleeding who had a total lower limb movement score of 3 points or less on the Stroke Impairment Assessment Set (SIAS) at the time of admission to the Kaifukuki rehabilitation ward (Kaifukuki ward). Survey items including age, gender, number of days from onset to Kaifukuki ward discharge, brain injury side, total lower limb movement of SIAS at the time of admission, tendon reflex, muscle tone, tactile sense, position sense, trunk verticality, abdominal muscle, visual space cognitive score, total motor and cognitive scores of functional independence measure, degree of damage to the corticospinal tract running area several days after the onset, amount of hematoma, and presence or absence of ventricular perforation were determined.Results: Multiple regression analysis was performed, with the degree of improvement in motor function as the dependent variable, and the item with significant correlation to the degree of improvement as the independent variable. The results of statistical analyses revealed that younger age, lower degree of damage to corticospinal tract running area, and higher SIAS trunk verticality score were significantly associated with the improvement of motor function.Conclusion: This study suggests that the sitting ability, in addition to the age and degree of damage to the corticospinal tract running area, are important in the assessment of physical therapy in order to predict the improvement of motor function in patients with severe motor disorders.